Evoking Context with Contrastive Stress: Effects on Pragmatic Enrichment - Cummins, Chris; Rohde, Hannah (Frontiers in Psychology, 2015)
Although it is widely acknowledged that context influences a variety of pragmatic phenomena, it is not clear how best to articulate this notion of context and thereby explain the nature of its influence. In this paper, we target contextual alternatives that are evoked via focus placement and test how the same contextual manipulation can influence three different phenomena that involve pragmatic enrichment: scalar implicature, presupposition, and coreference. We argue that focus placement influences these three phenomena indirectly by providing the listener with information about the likely question under discussion (QUD) that a particular utterance answers (Roberts, 1996/2012). In three listening experiments, we find that the predicted interpretations are indeed made more available when focus placement is added to the final element (to the scalar adjective, to an entity embedded under the negated presupposition trigger, and to the predicate of a pronoun). These findings bring together several distinct strands of work on the effect of focus placement on interpretation all in the domain of pragmatic enrichment. Together they advance our empirical understanding of the relation between focus placement and QUD and highlight commonalities between implicature, presupposition, and coreference.